Synthesis of single‐chain antibody fragment fused to the elastin‐like polypeptide in Nicotiana benthamiana and its application in affinity precipitation of difficult to produce proteins. Issue 9 (18th June 2022) - Marín Viegas, Vanesa S.; Ocampo, Carolina G.; Restucci, Fernando E.; Vignolles, Florencia; Mazzini, Flavia N.; Candreva, Ángela M.; Petruccelli, Silvana
Abstract: Plants are economical and sustainable factories for the production of recombinant proteins. Currently, numerous proteins produced using different plant‐based systems with applications as cosmetic and tissue culture ingredients, research and diagnostic reagents, and industrial enzymes are marketed worldwide. In this study, we aimed to demonstrate the usefulness of a plant‐based system to synthesize a single‐chain antibody (scFv)—elastin‐like polypeptide (ELP) fusion to be applied as an affinity precipitation reagent of the difficult to produce recombinant proteins. We used the human tissue transglutaminase (TG2), the main celiac disease autoantigen, as a proof of concept. We cloned a TG2‐specific scFv and fused it to a short hydrophobic ELP tag. The anti‐TG2‐scFv‐ELP was produced in Nicotiana benthamiana and was efficiently recovered by an inverse transition cycling procedure improved by coaggregation with bacteria‐made free ELP. Finally, the scFv‐ELP was used to purify both plant‐synthesized human TG2 and also Caco‐2‐TG2. In conclusion, this study showed for the first time the usefulness of a plant‐based expression system to produce an antibody‐ELP fusion designed for the purification of low‐yield proteins.